2002
DOI: 10.1007/s00213-002-1148-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mirtazapine on anterior pituitary hormone secretion in healthy male subjects

Abstract: Since the acute inhibition of COR secretion in the healthy volunteers was paralleled by a simultaneous decrease of ACTH release, central mechanisms (for example, inhibition of hypothalamic CRH output) are suggested to be responsible for the inhibitory effects of mirtazapine on COR secretion. Our results are of particular interest in the light of the hypercortisolism observed in depressed patients and new pharmacological approaches such as CRH(1) receptor antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 31 publications
(30 reference statements)
2
28
1
Order By: Relevance
“…The effects of mirtazapine on the sleep-related secretion of cortisol, GH, and prolactin resemble those reported after acute administration of the drug to normal control subjects at daytime (Laakmann et al, 1999;Schüle et al, 2002b). In accordance with these studies, we found a blunting of nocturnal cortisol levels throughout the night, whereas GH and prolactin secretion remained unchanged.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The effects of mirtazapine on the sleep-related secretion of cortisol, GH, and prolactin resemble those reported after acute administration of the drug to normal control subjects at daytime (Laakmann et al, 1999;Schüle et al, 2002b). In accordance with these studies, we found a blunting of nocturnal cortisol levels throughout the night, whereas GH and prolactin secretion remained unchanged.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to the decrease of nocturnal cortisol levels in the present study, salivary cortisol was blunted in depressed patients after 1 day of treatment (Laakmann et al, 2004). As discussed by Schüle et al (2002b), the antagonistic action of mirtazapine on alpha 2 , 5HT 2 , and H 1 receptors appears to contribute to the blunting of cortisol. In our study, ACTH secretion showed only a nonsignificant trend to decrease.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations